Smart Centralized Metering System for Commercial Building - Shrestha, Kiran; Yadav, Mitalesh Kumar; Aslami, Pooja; Pandit, Ram Ishwor; Tamrakar, Indraman (KEC Journal of Science and Engineering, 2023)
In commercial building, there are many shops in different floors. These shops are rented to different people and the electrical energy consumed by each shop has to be read every month. In conventional metering system, the meter reader has to go the metering panels in different floor which is time consuming and there is problem of raising the bill amount from the shop keepers in time and human error in meter reading. This paper presents a possible solution which is named as Smart Centralized Metering System for commercial building. The proposed system collects the data from each meter sends the data via wireless communication to a central server where monitoring and analysis of the data will be easily made. It will poll each and every individual shop automatically regularly in order to get the meter reading of the corresponding shop. If a particular shop did not pay the bill, power supply to the particular shop can be turned off from the server room. A proto type hardware of the scheme is fabricated and tested successfully.